The Promise of Percutaneous Transhepatic Variceal Embolization for Both Gastroesophageal and Ectopic Varices—An Australian Case Series - Ambati, Chaitanya; Danta, Mark; Boshell, David; Ende, Jesse; Williams, David; Chaganti, Joga (Journal of Clinical Interventional Radiology ISVIR, 2021)
Purpose This article aims to report Australian experience of percutaneous transhepatic embolization of gastroesophageal and ectopic varices.Method Eight consecutive patients (mean age 61.8 years, 7 men) who had undergone percutaneous transhepatic variceal embolization (PTVE) for variceal bleeding between October 2013 and February 2020 were analyzed. All patients were admitted from the emergency department. The following embolic materials were used—coils, Onyx 18 (Medtronic), and n-butyl cyanoacrylate plus lipiodol.Results Post-PTVE, all eight patients demonstrated clinical and radiological improvement in the immediate postprocedure period (< 24 hours). Patients were followed for a mean of 44 ± 24 days postprocedure. Two patients were lost to follow-up. The postprocedure complications included rebleeding (n = 1), hepatic encephalopathy (n = 1), hemoperitoneum (n = 1), ileus (n = 1), and abdominal pain (n = 3).Conclusion PTVE is an effective treatment option for patients with uncontrolled variceal bleeding (ectopic as well as gastroesophageal) especially when the traditional therapies such as transjugular intrahepatic portosystemic shunts, endoscopic variceal ligation, and balloon-occluded retrograde transvenous obliteration are contraindicated or ineffective.
Keywords: portal hypertension; transhepatic; embolization